Respuesta :
[tex]\qquad\qquad\huge\underline{{\sf Answer}}[/tex]
Let's evaluate ~
[tex]\qquad \sf \dashrightarrow \:(r + b - g)(b + g)[/tex]
Plug in the given values :
[tex]\qquad \sf \dashrightarrow \:(6 + 4 - 9)(4 + 9)[/tex]
[tex]\qquad \sf \dashrightarrow \:(1)(13)[/tex]
[tex]\qquad \sf \dashrightarrow \:13[/tex]
Hence, the equivalent value of given expression is 13
Answer:
(r + b - g)(b + g) = 13
Step-by-step explanation:
(r + b - g)(b + g)
- r = 6
- b =4
- g = 9
Substitute the numbers: (r + b - g)(b + g) ==> (6 + 4 - 9)(4 + 9)
Distribute (4 and 9):
4(6 + 4 - 9) + 9(6 + 4 - 9)
4(1) + 9(1)
4 + 9
Add:
4 + 9
13
Final answer: 13
Hope this helps!